Dependence of minority charge carriers lifetime on point defects type and their concentration in single-crystal silicon - Zaitsev, R. V.; Kirichenko, M. V.; Doroshenko, A. N.; Khrypunov, G. S. (Scientific and Technological Corporation "Institute for Single Crystals", 2011)
Using the computer simulation method it was studied the dependences of nonequili-brium electrons lifetime from concentration of elementary bulk point defects and various complexes of the bulk point defects, which may be present in the diode structures based on p-type conductivity boron doped silicon crystals with 10 Ohm-cm resistivity, grown by the Czochralski method. A number of obtained results well correlated with the experimental data related to the effects of photon degradation in solar cells which based on considered type silicon crystals (Si-SC) and influence of a stationary magnetic field on such devices efficiency. Overall, our results provide additional possibility for the evolution features prediction of electronic, and consequently, functional parameters, not only for Si-SC, but also for other devices based on such diode structures. It will allow looking for the most efficient and cost effective ways to optimize their design-technological solutions, and also estimates their reliability and durability level.

Методом комп’ютерного моделювання досліджено залежності часу життя нерівноважних електронів від концентрації елементарних об’ємних точкових дефектів та різноманітних комплексів об’ємних точкових дефектів, які можуть бути присутніми в діодних структурах на основі кристалів кремнію, легованих бором p-типу провідності. з питомим опором 10 Ом-см, вирощений методом Чохральського. Ряд отриманих результатів добре корелював з експериментальними даними щодо ефектів фотонної деградації в сонячних елементах на основі кристалів кремнію розглянутого типу (Si-SC) та впливу стаціонарного магнітного поля на ефективність таких пристроїв. Загалом, наші результати надають додаткові можливості для прогнозування еволюційних особливостей електронних, а отже, і функціональних параметрів не лише для Si-SC, але й для інших пристроїв на основі таких діодних структур. Це дозволить шукати найбільш ефективні та економічно вигідні шляхи оптимізації їх конструкторсько-технологічних рішень, а також оцінює рівень їх надійності та довговічності.
Залежність часу життя неосновних носіїв заряду від типу та концентрації точкових дефектів у монокристалічному кремнії
Keywords: single-crystal silicon; point defects; computer simulation; Czochralski method; magnetic field; хімічні реакції; комп'ютерне моделювання; електрони; фотоелектричні перетворювачі; метод Чохральського; магнітне поле